Modified asphalt-based hard carbon as well as preparation method and application thereof

In the field of sodium ion batteries, modified asphalt-based hard carbon is prepared by using the gradient temperature-raising reaction technology between asphalt and nitrogen-containing compounds, which solves the problem of insufficient electrochemical performance of asphalt-based hard carbon in the prior art, and achieves high rate performance and good cycle stability of sodium ion batteries.

CN119503766APending Publication Date: 2025-02-25WUHAN BISIDI BATTERY MATERIAL CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411540543.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the electrochemical performance of bituminous hard carbon materials still needs to be improved, especially in terms of rate performance and cycle stability of sodium ion batteries.

Method used

Modified asphalt-based hard carbon was prepared by mixing the asphalt with a nitrogen-containing compound, performing a gradient heating reaction under a protective gas atmosphere, introducing nitrogen doping, and then oxidation treatment, pre-carbonization and carbonization treatment. This method introduces nitrogen doping through gradient heating, adjusts the disordered structure of carbon materials, and builds a three-dimensional conductive network and flexible framework to improve electrochemical performance.

Benefits of technology

The rate performance and cycle stability of modified asphalt-based hard carbon in sodium ion batteries have been significantly improved, the charging specific capacity has increased, and the electrochemical performance has reached a higher level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503766A_ABST
    Figure CN119503766A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and discloses modified asphalt-based hard carbon as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing asphalt and a nitrogen-containing compound, carrying out a first heating reaction in a protective gas atmosphere, cooling, and carrying out a second heating reaction to obtain doped asphalt, carrying out oxidation treatment on the doped asphalt to obtain an oxidized material; and carrying out pre-carbonization and carbonization treatment on the oxidized material in a protective gas atmosphere to obtain the modified asphalt-based hard carbon. The doping of the gradient heating nitrogen element is beneficial to the construction of a three-dimensional conductive network and a flexible skeleton, and the conductivity and the structural stability of the modified asphalt-based hard carbon are enhanced, so that the electrochemical performance of the modified asphalt-based hard carbon is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a modified asphalt-based hard carbon and a preparation method and application thereof. Background Art

[0002] In recent decades, the rapid development of lithium-ion batteries has made them the most important energy storage device in daily life. However, lithium resources are limited, resulting in high costs for lithium-ion batteries. Sodium resources are relatively abundant compared to lithium resources, so sodium-ion batteries are gradually gaining attention due to their relatively low costs.

[0003] The performance of sodium-ion batteries depends largely on the electrode materials. As a key component of the battery, the negative electrode has an important impact on the practicality and cost of the battery. In the field of sodium-ion batteries, carbon-based materials, titanium-based materials, alloys, organic compounds, etc. are often used for the negative electrode. Among them, carbon-based materials have the advantages of high cost-effectiveness, high abundance, and adjustable structure. They are very promising negative electrode materials for sodium-ion batteries. Hard carbon has a highly amorphous structure with short-range graphitization. Compared with the graphite structure, the interlayer distance (0.37-0.42nm) of hard carbon is larger, and it has abundant pores and defects.

[0004] The precursor materials of hard carbon negative electrode materials for sodium ion batteries are mainly divided into four types: biomass precursors, sugar precursors, synthetic resin precursors, and asphalt precursors. Asphalt-based precursors have the advantages of low cost, high carbon content, and high carbon yield, and are considered to be potential carbon sources for synthesizing hard carbon negative electrodes. Asphalt is a byproduct of the coal or petroleum industry. It is mainly composed of a large number of polycyclic aromatic hydrocarbons (PAHs) and structurally related heterocyclic compounds. It has a low price and low ash content. It can be used to form nearly parallel carbon layers during heating to ensure high carbon yield and conductivity. However, direct pyrolysis of asphalt forms a microstructure with small interlayer spacing and high orientation during the uncontrollable liquid phase carbonization process, resulting in poor rate performance of sodium ion batteries. Studies have found that by modifying asphalt molecules, weakening or destroying the interaction between aromatics, the graphitization of asphalt can be interfered with and the transformation of the microstructure can be driven. The strategy of asphalt molecule modification is gradually moving towards the application of high-performance negative electrode materials. Model compounds such as quinoline or isoquinoline in asphalt can be used to prepare porous carbon under the catalysis of proton acid (HF / BF3) and Lewis acid (AlCl3) to improve electrochemical performance. At the same time, asphalt and cross-linked resins (phenolic, polyformaldehyde and furfuryl alcohol resins) or polymers (polypropylene, polysaccharides and butadiene-styrene copolymers) are co-carbonized to form disordered carbon with a high microporous structure.

[0005] There are various modification methods for pitch-based hard carbon materials in the prior art, but the electrochemical performance of the materials is usually to be improved. Therefore, it is urgent to provide a new pitch-based hard carbon material with further improved electrochemical performance. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a modified asphalt-based hard carbon and a preparation method and application thereof. The modified asphalt-based hard carbon of the present invention has high electrochemical performance.

[0007] A first aspect of the present invention provides a method for preparing a modified asphalt-based hard carbon, comprising the following steps:

[0008] Mixing asphalt with nitrogen-containing compounds, performing a first heating reaction under a protective gas atmosphere, then cooling, and then performing a second heating reaction to obtain doped asphalt;

[0009] The mixed asphalt is subjected to oxidation treatment to obtain an oxidized material;

[0010] The oxidized material is subjected to pre-carbonization and carbonization treatment under a protective gas atmosphere to obtain the modified asphalt-based hard carbon;

[0011] The insulation temperature of the second temperature-raising reaction is higher than the insulation temperature of the first temperature-raising reaction.

[0012] The second aspect of the present invention provides a modified asphalt-based hard carbon prepared by the above-mentioned preparation method.

[0013] The third aspect of the present invention provides an application of a modified asphalt-based hard carbon, and specifically relates to a sodium ion battery, comprising the modified asphalt-based hard carbon.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0015] (1) In the preparation method described in the present invention, a first temperature increase reaction is carried out, the temperature is lowered, and then a second temperature increase reaction is carried out, and the insulation temperature of the second temperature increase reaction is higher than the insulation temperature of the first temperature increase reaction. Such a gradient temperature increase is used to nitrogen-dope the asphalt, and then an oxidation treatment, pre-carbonization and carbonization treatment are carried out to obtain the modified asphalt-based hard carbon. Nitrogen doping can introduce defects and adjust the disordered structure of the carbon material during the carbonization process, which can hinder the effective development of long-range ordered carbon and the accumulation of graphite sheets, and provide sufficient active sites for the storage of sodium ions. In addition, the gradient temperature increase of nitrogen doping is conducive to the construction of a three-dimensional conductive network and a flexible skeleton, which enhances the conductivity and structural stability of the modified asphalt-based hard carbon, thereby improving the electrochemical performance of the modified asphalt-based hard carbon. In addition, different contents of nitrogen doping will result in certain differences in the electrochemical effects of the modified asphalt-based hard carbon obtained.

[0016] (2) The present invention performs nitrogen doping treatment on asphalt by gradient temperature increase, so that asphalt and nitrogen-containing compounds can better realize nitrogen atom doping in changing temperatures. Since nitrogen-containing compounds, such as melamine, are pyrolyzed in the temperature range of 200-500°C, melamine begins to decompose at 200°C in three stages, and these three stages are respectively the loss of one, two and three ammonia molecules for every two melamine molecules, corresponding to the formation of melamine, melem and melon, respectively. The present invention performs doping in stages, which can ensure sufficient doping, and can further cross-link the nitrogen-containing functional groups in the asphalt doped in the low temperature stage in the high temperature stage, thereby increasing the disorder and improving the ion conductivity of the modified asphalt-based hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a charge and discharge curve diagram of a button cell assembled from modified asphalt-based hard carbon in Example 1;

[0018] Figure 2 This is a specific capacity rate diagram of a button cell assembled from modified asphalt-based hard carbon in Example 1;

[0019] Figure 3 This is the specific capacity cycle diagram of the button battery assembled from the modified asphalt-based hard carbon in Example 1. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0021] In the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0022] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0023] In the present application, "at least one", "at least one" and other similar descriptions specifically refer to one or more, one or more; "multiple", "multiple" and other similar descriptions specifically refer to two or more, two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or plural, respectively.

[0024] A first aspect of the present invention provides a method for preparing a modified asphalt-based hard carbon, comprising the following steps:

[0025] Mixing asphalt with a nitrogen-containing compound, performing a first temperature-raising reaction under a protective gas atmosphere, then cooling, and then performing a second temperature-raising reaction to obtain a doped asphalt, wherein the insulation temperature of the second temperature-raising reaction is higher than the insulation temperature of the first temperature-raising reaction;

[0026] The mixed asphalt is subjected to oxidation treatment to obtain an oxidized material;

[0027] The oxidized material is subjected to pre-carbonization and carbonization treatment under a protective gas atmosphere to obtain the modified asphalt-based hard carbon.

[0028] Specifically, the present invention provides a method for preparing a modified asphalt-based hard carbon, comprising the following steps:

[0029] Step S11: mixing the asphalt and the nitrogen-containing compound, performing a first temperature-raising reaction under a protective gas atmosphere, then cooling, and then performing a second temperature-raising reaction to obtain a doped asphalt, wherein the insulation temperature of the second temperature-raising reaction is higher than the insulation temperature of the first temperature-raising reaction;

[0030] Step S12: subjecting the mixed asphalt to oxidation treatment to obtain an oxidized material;

[0031] Step S13: Under a protective gas atmosphere, the oxidized material is subjected to pre-carbonization and carbonization treatment to obtain the modified asphalt-based hard carbon.

[0032] In the preparation method of the present invention, the asphalt is nitrogen-doped by a gradient heating process such as a first heating reaction, cooling, and then a second heating reaction, and then oxidation treatment, pre-carbonization and carbonization treatment are performed to obtain the modified asphalt-based hard carbon. Nitrogen doping can introduce defects and adjust the disordered structure of carbon materials during the carbonization process, which can hinder the effective development of long-range ordered carbon and the accumulation of graphite sheets, and provide sufficient active sites for the storage of sodium ions. In addition, the doping of nitrogen elements is conducive to the construction of a three-dimensional conductive network and a flexible skeleton, which enhances the conductivity and structural stability of the modified asphalt-based hard carbon, thereby improving the electrochemical properties of the modified asphalt-based hard carbon.

[0033] In step S11:

[0034] In some embodiments of the present invention, the asphalt includes coal tar or petroleum tar. The use of coal tar helps to reduce production costs. Further, the softening point of the asphalt is not less than 180°C, for example, the softening point is 200-300°C, more specifically, for example, 180°C, 200°C, 280°C, 300°C. The sulfur content of the asphalt is less than 0.1wt% (wt% means weight percentage), for example, 0.01wt%-0.08wt%. Low sulfur content is conducive to reducing the adverse effects of impurities on the electrochemical performance of modified asphalt-based hard carbon.

[0035] In some embodiments of the present invention, the D of the asphalt 50 Less than or equal to 10 μm. For example, less than or equal to 9 μm, specifically 1 μm, 5 μm, 6 μm, 9 μm. Smaller particle size helps to increase the contact area between asphalt and nitrogen-containing compounds, making the reaction more complete.

[0036] In some embodiments of the present invention, the nitrogen-containing compound includes melamine or urea.

[0037] In some embodiments of the present invention, the mass ratio of the nitrogen-containing compound to the asphalt is (5-15):100, further (10-15):100. Specifically, for example, 5:100, 10:100, 15:100. Different amounts of nitrogen doping will result in certain differences in the electrochemical effects of the modified asphalt-based hard carbon.

[0038] In some embodiments of the present invention, the protective gas atmosphere includes at least one of nitrogen or a rare gas, and the rare gas may be, for example, at least one of helium, argon, krypton or xenon.

[0039] In some embodiments of the present invention, the insulation temperature of the first temperature-raising reaction is 180-220°C, for example, 190-210°C. Specifically, it can be 180°C, 190°C, 200°C, 210°C, or 220°C.

[0040] In some embodiments of the present invention, the insulation reaction time of the first temperature-raising reaction is 1-3 hours, and specifically can be 1 hour, 2 hours, or 3 hours.

[0041] In some embodiments of the present invention, the cooling is to room temperature.

[0042] In some embodiments of the present invention, the insulation temperature of the second temperature-raising reaction is 280-300°C, for example, 290-300°C. Specifically, it can be 280°C, 290°C, or 300°C.

[0043] In some embodiments of the present invention, the insulation reaction time of the second temperature-raising reaction is 1-3 hours, and specifically can be 1 hour, 2 hours, or 3 hours.

[0044] It can be understood that the gradient temperature increase in this step is specifically: firstly, the temperature is increased from room temperature to the insulation temperature of the first temperature increase reaction, after a period of insulation reaction, the temperature is cooled to room temperature, and then the temperature is increased from room temperature to the insulation temperature of the second temperature increase reaction (the temperature is higher than the insulation temperature of the first temperature increase reaction), after a period of insulation reaction, the temperature is cooled to room temperature. The asphalt doped with nitrogen-containing compounds has undergone a cooling and heating stage starting from room temperature again, which can promote the increase of the actual nitrogen doping ratio and promote the construction of a three-dimensional conductive network and a flexible skeleton, and improve the conductivity and structural stability of the modified asphalt-based hard carbon, as well as the capacity and rate.

[0045] Furthermore, after the first temperature-raising reaction is cooled to room temperature, the asphalt may be crushed or broken, and then subjected to a second temperature-raising reaction, thereby further improving the uniformity and thermal sufficiency of nitrogen doping.

[0046] The present invention performs nitrogen doping in stages, which can ensure sufficient doping and enable the nitrogen-containing functional groups in the doped asphalt in the low-temperature stage to further cross-link in the high-temperature stage, thereby increasing the disorder and improving the ion conductivity of the modified asphalt-based hard carbon.

[0047] It can be understood that the mixing method may include known mixing methods such as stirring or ultrasound.

[0048] In step S12:

[0049] In some embodiments of the present invention, the oxidation treatment is carried out in an air environment at 280-320° C. for 2-4 hours, followed by crushing, and then in an air environment at 280-320° C. for 2-4 hours, crushing again, and then in an air environment at 280-320° C. for 2-4 hours. Multiple crushing and oxidation treatments allow the obtained oxidized material to be fully and evenly oxidized.

[0050] In step S13:

[0051] In some embodiments of the present invention, the temperature of the pre-carbonization treatment is 400-900° C., for example, 600-750° C. The time of the pre-carbonization treatment can be 1-5 hours, for example, 2-3 hours.

[0052] In some embodiments of the present invention, after the pre-carbonization treatment is completed, the obtained pre-carbonized material is crushed. For example, crushed to D 50 To 1-10μm, more specific D 50 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, and 10μm.

[0053] In some embodiments of the present invention, the temperature of the carbonization treatment is 1200-1700°C, and the time is 0.5-4 hours. Specifically, the temperature of the carbonization treatment can be 1200-1300°C, 1300-1500°C, 1500-1700°C, etc. The time of the carbonization treatment can be 0.5-1 hour, 1-2 hours, 2-3 hours, 3-4 hours, etc.

[0054] In some embodiments of the present invention, after step S13, that is, after the carbonization treatment is completed, a coating treatment is further included, and the coating treatment process includes: mixing the material after the carbonization treatment with the coating asphalt, and then coating the material under a protective gas atmosphere to obtain a modified asphalt-based hard carbon. The coating treatment can reduce the surface defects of the material obtained after the carbonization, thereby improving the electrochemical performance of the modified asphalt-based hard carbon (for example, improving the charge specific capacity).

[0055] Specifically, the coating asphalt can be selected from petroleum asphalt with a softening point of 220-280° C. The mass of the coating asphalt used is 5%-12% of the mass of the material after carbonization treatment. For example, 5%-10%. Specifically, for example, 5%, 10%, 12%.

[0056] In some embodiments of the present invention, the coating treatment is performed at a temperature of 1200-1700° C. for 1-3 hours. Further, the coating treatment is performed at a temperature of 1300-1500° C. for 0.5-1.5 hours.

[0057] In some embodiments of the present invention, the coating process further includes a crushing process, wherein the material after the carbonization process and the coated asphalt are mixed and crushed to D 50 The thickness is 2-9 μm, for example, 3-9 μm, more specifically, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, and 9 μm.

[0058] The second aspect of the present invention provides a modified asphalt-based hard carbon prepared by the above-mentioned preparation method.

[0059] The third aspect of the present invention provides an application of a modified asphalt-based hard carbon, which can be specifically applied to sodium ion batteries, for example, it can be used as a negative electrode material of a sodium ion battery.

[0060] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0061] Example 1

[0062] A method for preparing modified asphalt-based hard carbon comprises the following steps:

[0063] Step (1): Gradient temperature doping

[0064] Mix asphalt (softening point of 200°C, sulfur content less than 0.1wt%) with melamine (D 50 The first temperature-raising reaction was carried out under a protective gas atmosphere (nitrogen), the insulation temperature of the first temperature-raising reaction was 200°C, the insulation time of the first temperature-raising reaction was 2h, then the mixture was cooled to room temperature and crushed, and the second temperature-raising reaction was carried out, the insulation temperature of the second temperature-raising reaction was 280°C, the insulation time of the second temperature-raising reaction was 2h, and the doped asphalt was obtained;

[0065] Step (2): Oxidation treatment

[0066] The doped asphalt obtained in step (1) is placed in a muffle furnace (in an air environment), oxidized at 300° C. for 2 hours, then crushed, and oxidized again in a muffle furnace (in an air environment) at 300° C. for 2 hours, crushed again, and oxidized again in a muffle furnace (in an air environment) at 300° C. for 2 hours to obtain an oxidized material;

[0067] Step (3): Pre-carbonization

[0068] The oxidized material obtained in step (2) is added into a tubular furnace, heated to 700° C. under the protection of an inert gas (nitrogen) for pre-carbonization treatment for 2 h, and the cooled block is crushed to obtain a pre-carbonized material powder;

[0069] Step (4): Carbonization

[0070] The pre-carbonized material powder obtained in step (3) is placed in a tubular furnace, and the temperature is raised to 1300° C. for high-temperature carbonization treatment for 2 h under the protection of an inert gas (nitrogen) to obtain a powdered carbon material;

[0071] Step (5): Coating

[0072] The carbon material obtained in step (4) is mixed with coated asphalt (the coated asphalt is petroleum asphalt with a softening point of 220°C, and the weight of the coated asphalt is 10% of the carbon material), and the mixture is fully crushed and mixed by a powder grinder to control the particle size D 50 The mixture is then placed in a tubular furnace and heated to 1300°C under the protection of an inert gas (nitrogen) for coating treatment for 1 hour to obtain modified asphalt-based hard carbon.

[0073] Example 2

[0074] Compared with Example 1, the only difference of Example 2 is that the mass ratio of melamine to asphalt in step (1) is 5:100, and the rest of the process is the same as Example 1.

[0075] Example 3

[0076] Compared with Example 1, the only difference of Example 3 is that the mass ratio of melamine to asphalt in step (1) is 15:100, and the rest of the process is the same as Example 1.

[0077] Example 4

[0078] Compared with Implementation 1, the difference of Implementation 4 is that step (1) is different from step (1) of Implementation 1, and the rest of the process is the same as Implementation 1.

[0079] The specific contents of step (1) of Example 4 are as follows:

[0080] Mix asphalt (softening point of 200°C, sulfur content less than 0.1wt%) with melamine (D 50 The particle size of the particles is 6 μm, the mass ratio of melamine to asphalt is 10:100, and the first temperature rising reaction is carried out under a protective gas atmosphere (nitrogen). The insulation temperature of the first temperature rising reaction is 180°C, and the insulation time of the first temperature rising reaction is 3 hours. The particles are then cooled to room temperature and crushed. The second temperature rising reaction is carried out. The insulation temperature of the second temperature rising reaction is 320°C, and the insulation time of the second temperature rising reaction is 1 hour to obtain doped asphalt.

[0081] Example 5

[0082] Compared with Implementation 1, the difference between Implementation 5 and Embodiment 1 is that step (1) is different from step (1) of Embodiment 1, and the rest of the process is the same as Embodiment 1.

[0083] The specific contents of step (1) of Example 5 are as follows:

[0084] Mix asphalt (softening point of 200°C, sulfur content less than 0.1wt%) with melamine (D 50The particle size of the particles is 6 μm, the mass ratio of melamine to asphalt is 10:100, and the first temperature rising reaction is carried out under a protective gas atmosphere (nitrogen). The insulation temperature of the first temperature rising reaction is 220°C, and the insulation time of the first temperature rising reaction is 1 hour. The particles are then cooled to room temperature and crushed. The second temperature rising reaction is carried out. The insulation temperature of the second temperature rising reaction is 280°C, and the insulation time of the second temperature rising reaction is 3 hours to obtain doped asphalt.

[0085] Example 6

[0086] A method for preparing modified asphalt-based hard carbon comprises the following steps:

[0087] Step (1): Gradient temperature doping

[0088] Mix asphalt (softening point of 200°C, sulfur content less than 0.1wt%) with urea (D 50 The mass ratio of urea to asphalt is 10:100, and the first temperature-raising reaction is carried out under a protective gas atmosphere (nitrogen), the insulation temperature of the first temperature-raising reaction is 200°C, the insulation reaction time of the first temperature-raising reaction is 2h, and then it is cooled to room temperature and crushed, and then the second temperature-raising reaction is carried out, the insulation temperature of the second temperature-raising reaction is 280°C, and the insulation reaction time of the second temperature-raising reaction is 2h, to obtain doped asphalt;

[0089] Step (2): Oxidation treatment

[0090] The doped asphalt obtained in step (1) is placed in a muffle furnace (in an air environment), subjected to oxidation treatment at 280° C. for 2 hours, then crushed, and then subjected to oxidation treatment at 280° C. for 2 hours in a muffle furnace (in an air environment), crushed again, and then subjected to oxidation treatment at 280° C. for 2 hours in a muffle furnace (in an air environment) to obtain an oxidized material;

[0091] Step (3): Pre-carbonization

[0092] The oxidized material obtained in step (2) is added into a tubular furnace, heated to 600° C. under the protection of an inert gas (nitrogen) for pre-carbonization treatment for 2 h, and the cooled block is crushed to obtain a pre-carbonized material powder;

[0093] Step (4): Carbonization

[0094] The pre-carbonized material powder obtained in step (3) is placed in a tubular furnace, and heated to 1400° C. for high-temperature carbonization treatment for 2 h under the protection of an inert gas (nitrogen) to obtain a powdered carbon material;

[0095] Step (5): Coating

[0096] The carbon material obtained in step (4) is mixed with coated asphalt (the coated asphalt is petroleum asphalt with a softening point of 220°C, and the weight of the coated asphalt is 10% of the carbon material), and the mixture is fully crushed and mixed by a powder grinder to control the particle size D 50 The mixture is then placed in a tubular furnace and heated to 1400°C under the protection of an inert gas (nitrogen) for coating treatment for 1 hour to obtain modified asphalt-based hard carbon.

[0097] Comparative Example 1

[0098] Compared with Implementation 1, the difference of Comparative Example 1 is that step (1) is different from step (1) of Example 1, and the rest of the process is the same as Example 1.

[0099] The specific contents of step (1) of Comparative Example 1 are as follows:

[0100] Mix asphalt (softening point of 200°C, sulfur content less than 0.1wt%) with melamine (D 50 The mass ratio of melamine to asphalt was 10:100, and the reaction was carried out at 200°C for 4 hours under a protective gas atmosphere (nitrogen) to obtain doped asphalt.

[0101] Comparative Example 2

[0102] Compared with Implementation 1, the difference of Comparative Example 2 is that step (1) is different from step (1) of Example 1, and the rest of the process is the same as Example 1.

[0103] The specific contents of step (1) of Comparative Example 2 are as follows:

[0104] Mix asphalt (softening point of 200°C, sulfur content less than 0.1wt%) with melamine (D 50 The mass ratio of melamine to asphalt is 10:100, and a temperature reaction is carried out under a protective gas atmosphere (nitrogen). The insulation temperature of the temperature reaction is 280°C and the insulation time of the temperature reaction is 4h to obtain doped asphalt.

[0105] Comparative Example 3

[0106] Compared with Implementation 1, the difference of Comparative Example 3 is that step (1) is different from step (1) of Example 1, and the rest of the process is the same as Example 1.

[0107] The specific contents of step (1) of Comparative Example 3 are as follows:

[0108] Mix asphalt (softening point of 200°C, sulfur content less than 0.1wt%) with melamine (D 50The mass ratio of melamine to asphalt is 10:100, and the first temperature rising reaction is carried out under a protective gas atmosphere (nitrogen). The insulation temperature of the first temperature rising reaction is 200°C, and the insulation reaction time of the first temperature rising reaction is 2h. Then the second temperature rising reaction is carried out, and the insulation temperature of the second temperature rising reaction is 280°C, and the insulation reaction time of the second temperature rising reaction is 2h to obtain doped asphalt.

[0109] Product effect testing

[0110] The modified asphalt-based hard carbons obtained in the above Examples 1-6 and Comparative Examples 1-3 were respectively prepared into button-type batteries.

[0111] The specific steps for preparing button batteries are as follows: Modified asphalt-based hard carbon is mixed with conductive carbon Super-P and PVDF (polyvinylidene fluoride) in a mass ratio of 92:3:3, and then N-methylpyrrolidone (NMP) is used as solvent. After mixing evenly, it is coated on aluminum foil and dried in a vacuum oven at 102°C. After rolling, it is cut into circular electrode pieces with a diameter of 8 mm, with sodium sheets as the negative electrode, the electrolyte is a NaPF6 lipid electrolyte of model NP-001, and the diaphragm is a glass fiber diaphragm. The button batteries are assembled in a glove box filled with argon.

[0112] The charge and discharge performance of the prepared button battery was tested. The battery test adopted the Xinwei battery testing system. The test method adopted constant current and constant voltage discharge and constant current charging. The charge and discharge test was carried out at a current density of 0.1C. The discharge cut-off voltage was 0V and the charge cut-off voltage was 2.5V. The results are shown in Table 1 (charge and discharge efficiency = charge specific capacity / discharge specific capacity*100%).

[0113] Table 1

[0114]

[0115]

[0116] It can be seen from Table 1 that the charging specific capacities corresponding to Examples 1-6 of the present invention are significantly higher than those of Comparative Examples 1-3.

[0117] Compared with Example 1, in Comparative Examples 1-2, asphalt and melamine react at the same temperature and are not subjected to gradient heating, so that the prepared modified asphalt-based hard carbon has a significantly lower charge capacity than Example 1. Although Comparative Example 3 involves gradient heating, there is no cooling process between the two heatings, resulting in the modified asphalt-based hard carbon prepared in Comparative Example 3 having a significantly lower charge capacity than Example 1. The gradient heating process of Example 1 of the present invention is to carry out nitrogen doping in stages, which can ensure sufficient doping, and can allow the nitrogen-containing functional groups in the doped asphalt in the low-temperature section to further cross-link in the high-temperature section, increase the degree of disorder, and improve the conductivity of the modified asphalt-based hard carbon to ions, thereby improving the electrochemical performance of the modified asphalt-based hard carbon. However, Comparative Examples 1-2 are doped only at one insulation temperature, resulting in insufficient doping or insufficient cross-linking reaction of the nitrogen-containing functional groups, and the degree of disorder of the product is reduced, thereby reducing the electrochemical performance of the modified asphalt-based hard carbon. In Comparative Example 3, doping is carried out at two consecutive heating insulation temperatures, lacking a cooling process in between and a heating stage from room temperature again, which is not conducive to constructing a three-dimensional conductive network and a flexible skeleton, and reduces the conductivity and structural stability of the modified asphalt-based hard carbon, thereby reducing the electrochemical properties of the modified asphalt-based hard carbon.

[0118] Figure 1 This is a charge and discharge curve diagram of a button cell assembled from modified asphalt-based hard carbon in Example 1; Figure 2 The specific capacity rate diagram of the button cell assembled from the modified asphalt-based hard carbon in Example 1; Figure 2 It can be seen that the modified asphalt-based hard carbon in Example 1 has good rate performance.

[0119] Figure 3 This is a specific capacity cycle diagram of a button cell assembled with modified asphalt-based hard carbon in Example 1. It can be seen from the diagram that the modified asphalt-based hard carbon in Example 1 has good cycle stability.

Claims

1. A method for preparing modified asphalt-based hard carbon, characterized in that: The following steps are involved: Mixing asphalt with nitrogen-containing compounds, performing a first heating reaction under a protective gas atmosphere, then cooling, and then performing a second heating reaction to obtain doped asphalt; The mixed asphalt is subjected to oxidation treatment to obtain an oxidized material; The oxidized material is subjected to pre-carbonization and carbonization treatment under a protective gas atmosphere to obtain the modified asphalt-based hard carbon; The insulation temperature of the second temperature-raising reaction is higher than the insulation temperature of the first temperature-raising reaction.

2. The preparation method according to claim 1, characterized in that: The asphalt includes coal asphalt or petroleum asphalt; and / or, the softening point of the asphalt is not less than 180°C; and / or, the sulfur content of the asphalt is less than 0.1 wt%; and / or, the D of the asphalt 50 Less than or equal to 10μm; And / or, the nitrogen-containing compound comprises melamine or urea.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the nitrogen-containing compound to the asphalt is (5-15):100; And / or, the protective gas atmosphere includes at least one of nitrogen or a rare gas, and the rare gas is at least one of helium, argon, krypton or xenon; And / or, the insulation temperature of the first temperature-raising reaction is 180-220° C.; And / or, the insulation reaction time of the first temperature-raising reaction is 1-3h; And / or, the cooling is to room temperature; And / or, the insulation temperature of the second temperature-raising reaction is 280-300° C.; And / or, the insulation reaction time of the second temperature rising reaction is 1-3h.

4. The preparation method according to claim 1, characterized in that: The oxidation treatment is carried out at 280-320° C. for 2-4 hours in an air environment, followed by crushing, and then oxidizing at 280-320° C. for 2-4 hours in an air environment, crushing again, and continuing to oxidize at 280-320° C. for 2-4 hours in an air environment.

5. The preparation method according to claim 1, characterized in that: The pre-carbonization temperature is 400-900°C; And / or, the pre-carbonization time is 1-5h; and / or, after the pre-carbonization treatment is completed, the obtained pre-carbonized material is crushed; And / or, the carbonization temperature is 1200-1700° C., and the time is 0.5-4 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that: After the carbonization treatment is completed, a coating treatment is also included. The coating treatment process includes: mixing the material after the carbonization treatment with coating asphalt, and then performing the coating treatment under a protective gas atmosphere to obtain the modified asphalt-based hard carbon.

7. The preparation method according to claim 6, characterized in that: The coating asphalt is selected from petroleum asphalt with a softening point of 220-280°C; and / or, the mass of the coated asphalt is 5%-12% of the mass of the material after the carbonization treatment; And / or, the coating treatment is carried out at a temperature of 1200-1700° C. and for a time of 1-3 hours.

8. The preparation method according to claim 6, characterized in that: The coating process also includes a crushing process before the carbonization process, wherein the material mixed with the coated asphalt is crushed to D 50 2-9μm.

9. A modified asphalt-based hard carbon, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: Comprising the modified asphalt-based hard carbon as described in claim 9.

Citation Information

Cited By

  • Hard carbon negative electrode material and preparation method and application thereof

    CN120398033A

  • Nitrogen-doping-regulated coal pitch-based potassium ion battery negative electrode material and preparation method thereof

    CN121698323A

  • Quinoline insoluble substance in-situ reconstruction-based regenerated graphite negative electrode asphalt coating method, regenerated graphite negative electrode material and lithium ion battery

    CN122599580A